2021
DOI: 10.1002/er.7292
|View full text |Cite
|
Sign up to set email alerts
|

State‐of‐healthestimation for the lithium‐ion battery based on gradient boosting decision tree with autonomous selection of excellent features

Abstract: The prediction of the health status and remaining useful life of lithium-ion batteries is very important for the safety of electric vehicles and other devices.However, due to the fact that battery residual capacity cannot be measured in real time, the estimation of battery health status is a great challenge for the management system of electric vehicles. At present, machine learning methods have been widely used in battery health state estimation. Based on the experimental data of NASA lithium-ion battery, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…23,24 Benefiting from the rapid development of the machine learning (ML) technology, scholars can readily achieve SOH estimation by employing the support vector machine (SVM), the Gaussian process regression (GPS), the decision tree (DT), the neural network (NN), etc. [25][26][27][28] Among them, owing to the strong learning ability and scalability, various NN-based methods obtain a slew of attentions. 29,30 After feature selection and extraction, the NN-based methods can realize efficient estimation by inferring the relationship between the input and output.…”
Section: The Soh Estimation Methodsmentioning
confidence: 99%
“…23,24 Benefiting from the rapid development of the machine learning (ML) technology, scholars can readily achieve SOH estimation by employing the support vector machine (SVM), the Gaussian process regression (GPS), the decision tree (DT), the neural network (NN), etc. [25][26][27][28] Among them, owing to the strong learning ability and scalability, various NN-based methods obtain a slew of attentions. 29,30 After feature selection and extraction, the NN-based methods can realize efficient estimation by inferring the relationship between the input and output.…”
Section: The Soh Estimation Methodsmentioning
confidence: 99%
“…It can classify and predict data, and it possesses advantages such as high accuracy, low computational cost, and high interpretability [17]. Based on the NASA LIB charge-discharge experimental data, Zhang et al [18] proposed a model based on the gradient-boosting decision trees model framework to achieve evaluation of LIB SOH; Salinas et al [19] predicted the SOH of an aging battery based on an enhanced decision trees model and analyzed its influencing factors; Wang et al [20] used DTs to analyze the adaptability of battery to working condition, temperature and degradation, and found that the dynamic characteristics of battery changed significantly during aging.…”
Section: Introductionmentioning
confidence: 99%
“…1 The high-precision battery-state estimation method is needed to develop a more efficient BMS. 2 Battery states include the state of charge (SOC) 3,4 state of energy (SOE), 5 state of health (SOH), 6 and state of power (SOP). 7 These battery states must be estimated accurately to prevent safety concerns, improve performance, and increase battery life.…”
Section: Introductionmentioning
confidence: 99%